Fiscal decentralization in centralized states: The case of Central Asia - Natalie Leschenko; Manuela Troschke (Osteuropa-Institut München, 2006)
The resource-based Central Asian countries Kazakhstan, Turkmenistan, and Uzbekistan constitute a special case for fiscal decentralization. Political and administrative centralization is accompanied by the centralized administration of resource rents and weak governance structures on local levels. Following best practices, fiscal decentralization is on the reform agenda in all three transition countries. As advocated in economic literature and indicated in empirical evidence, policymakers expect positive results on macroeconomic outcomes as well as on overall state governance. But the mechanism for the positive effects of fiscal decentralization is the creation of appropriate incentives by transferring information rights and authority to the local levels. How do the centralized states of Central Asia apply fiscal decentralization and what are the outcomes of their policies? To answer this question, we analyze the progress of fiscal decentralization in Kazakhstan, Uzbekistan, and Turkmenistan since independence. In all three countries we observe high levels of fiscal decentralization. The de-facto institutional design of fiscal decentralization, however, is not appropriate to make incentive mechanisms work. Fiscal autonomy at the revenue and expenditure side is almost absent, and the transfer system lacks transparency and predictability. Administrative and political centralization are the drivers of this institutional design and create obstacles for the merits of fiscal decentralisation to materialize.
Keywords: 330